UNDP's Multidimensional poverty index - Jean-Yves Duclos (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
The measurement of well-being in its multidimensional aspects has become ever more prominent in monitoring development over the last three decades. This note discusses some of the properties of a recent multidimensional index proposed by the UNDP. Unlike most of its predecessors, UNDP's Multidimensional Poverty Index (MPI) succeeds in taking into account both the distribution of deprivation within a number of dimensions as well as the distribution of multiple deprivations across the dimensions. This is important since there are good reasons to think of multidimensional poverty as more than just the sum of poverty across various dimensions of well-being. The MPI suffers, however, from a few unattractive features that need to be better understood (given the recently acquired prominence of the index). The object of this note is to highlight some of them.
Keywords: D31; D63; I32; O15; 330